Clinical features of acute pancreatitis with metabolic syndrome and influencing factors for prognosis - ZHONG Rui (Linchuang Gandanbing Zazhi, 2020)
ObjectiveTo investigate the clinical features of acute pancreatitis (AP) with metabolic syndrome (MS) and the influencing factors for prognosis. MethodsA retrospective analysis was performed for the clinical data of 590 patients with AP who were admitted to The Affiliated Hospital of Southwest Medical University from January 2013 to January 2019, and according the presence or absence of MS, they were divided into MS group with 178 patients and non-MS group with 412 patients and basic clinical features were compared between the two groups. According to the severity of AP, they were divided into mild acute pancreatitis (MAP) group with 317 patients, moderate-severe acute pancreatitis (MSAP) group with 171 patients, and severe acute pancreatitis (SAP) group with 102 patients, and the component indicators of MS were compared between the three groups. The t-test was used for comparison of normally distributed continuous data between two groups, and a one-way analysis of variance was used for comparison between multiple groups; the Mann-Whitney U test was used for comparison of non-normally distributed continuous data between two groups, and the Kruskal-Wallis H test was used for comparison between multiple groups; Bonferroni correction was used for further comparison between two groups. The chi-square test was used for comparison of categorical data between groups; the trend chi-square test was used for comparison of one-way ordinal categorical data, and the Goodman-Kruskal Gamma analysis was used for two-way ordinal categorical data. An ordinal logistic regression analysis was used to investigate the correlation between body mass index (BMI) and severity of AP, and a binary logistic regression analysis was used to investigate the correlation between MS and severity of AP. ResultsThe most common causes of MS with AP were hyperlipidemia (48.3%) and biliary disease (24.7%). The patients with SAP were more likely to have MS (χ2=141.519, P＜0.001), and the patients with AP and MS tended to have a significantly higher clinical system score, significantly more local and systemic complications, significantly longer hospital stays, a significantly higher ICU admission rate, and a significantly higher mortality rate (all P＜0.05). The severity of AP increased with the increase in MS components (overweight, hypertension, diabetes, and dyslipidemia), (G=0.540, P＜0.001). There were significant differences between the MAP, MSAP, and SAP groups in BMI (F=9.291, P＜0.001) and high-density lipoprotein cholesterol (HDL-C) (χ2=40.351, P＜0.001), and the SAP group had significantly higher BMI and significantly lower HDL-C than the MAP group and the MSAP group (all P＜0.05). The ordinal logistic regression analysis showed that BMI was an independent risk factor for the progression of AP (odds ratio ［OR］=1.091, 95% confidence interval ［CI］: 1.041-1.143, P＜0.001). Binary logistic regression models were established based on the severity of AP, with MAP group versus non-MAP group as model 1 and SAP group versus non-SAP group as model 2. The results showed that in model 1, the incidence rate of non-MAP was 5.867 times that of MAP in patients with MS (OR=5867, 95% CI: 3.072-11.207, P＜0.001), and in model 2, the incidence rate of SAP was 7.214 times that of non-SAP (OR=7.214, 95% CI: 3.018-17.244, P＜0.001). Both model 1 and model 2 showed that HDL-C was a protective factor against the progression of AP (model 1: OR=0.593, 95% CI: 0.387-0.910, P=0.017; model 2: OR=0.314, 95% CI: 0.160-0.614, P=0.001). ConclusionAP with MS on admission may suggest poor prognosis, and BMI and HDL-C are closely associated with disease progression.